Effect of Pulsed Electric Fields on the Growth and Acidification Kinetics of Lactobacillus delbrueckii Subsp. bulgaricus - Peng, Kaidi (Foods, 2020)
The aim of this work was to investigate the effect of pulsed electric fields (PEF) on the growth and acidification kinetics of Lactobacillus delbrueckii subsp. bulgaricus CFL1 during fermentation. The PEF treatments were applied during the fermentation process using a recirculation pump and a PEF treatment chamber coupled with a PEF generator. The medium flow rate through the chamber was first optimized to obtain the same growth and acidification kinetics than the control fermentation without medium recirculation. Different PEF intensities (60–428 V cm(−1)) were then applied to the culture medium to study the impact of PEF on the cells’ behavior. The growth and acidification kinetics were recorded during the fermentation and the specific growth rates µ, pH, and acidification rate (dpH/dt) were assessed. The results obtained showed a biphasic growth by applying high PEF intensities (beyond 285 V cm(−1)) with the presence of two maximal specific growth rates and a decrease in the acidification activities. It was demonstrated that the cells were stressed during the PEF treatment, but presented an accelerated growth after stopping it, leading thereby to similar absorbance and pH at the end of the fermentation. These results show the great potential of PEF technology to be applied to generate low acidified products by performing PEF-assisted fermentations.